Hubungan Empiris Parameter Koefisien Konsolidasi Cv, Dan Konsolidasi Ch (Studi Kasus: Tanah Pesisir Provinsi Riau) - Rahman, Sayful; Fatnanta, Ferry; Yusa, M. (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The rapid development of infrastructure in Riau Province has an impact on increasing land needs, especially in coastal areas which are dominated by soft soils. Soft soil will experience a large settlement if it is given a construction load for a long time. This is caused by the discharge of pore water in the soil causing damage to the construction structure. The preloading method on soft soil with vertical drain system is one of the most popular methods used to increase the shear strength of soft soil and control the settlement that occurs after construction. The permeability rate of soft soil is very low so that the time for consolidation to achieve the optimum shear strength will take more time. Generally, consolidation occurs only in the vertical direction, whereas in this study horizontal consolidation is obtained by modifying the consolidation test, namely by using a membrane to limit the movement of pore water when compressed by loading so that the water moves radially towards the vertical hole that filled with sand. This study aims to analyze the relationship between the vertical consolidation coefficient and the horizontal consolidation coefficient on the physical properties of the soil through laboratory tests. Soil samples used in this study were taken in undisturbed conditions. The results of this study obtained differences in the decline that occurred in various types of soil from the coastal areas of Riau Province. The largest land subsidence for vertical consolidation and horizontal consolidation is on the Pakning River. Based on the results of testing that has been done, the correlation coefficient cv and coefficient ch, is obtained by means of linear regression. Correlation of coefficient cv and coefficient ch obtained empirical correlation value in an equation ch = 11.088cv + 0.0005. Keywords : Soft Soil, Vertical Drain, Vertical Consolidation, Horizontal Consolidation, Square Root of Time Method.